Anti-AAV Antibodies in AAV Gene Therapy: Current Challenges and Possible Solutions - Weber, Thomas (Frontiers in Immunology, 2021)
Adeno-associated virus (AAV) vector-based gene therapy is currently the only in vivo gene therapy approved in the US and Europe. The recent tragic death of three children in a clinical trial to treat X-Linked Myotubular Myopathy by delivering myotubularin with an AAV8 vector notwithstanding, AAV remains a highly promising therapeutic gene delivery platform. But the successful use of AAV vectors to treat an increasing number of diseases also makes establishing protocols to determine therapeutically relevant titers of pre-existing anti-AAV antibodies and approaches to deplete those antibodies more urgent than ever. In this mini review, I will briefly discuss i) our knowledge regarding the prevalence of anti-AAV antibodies, ii) the challenges to measure those antibodies by methods that are most predictive of their influence on therapeutic efficacy of AAV gene transfer and iii) approaches to overcome the formidable hurdle that anti-AAV antibodies pose to the successful clinical use of AAV gene therapy.